Changes in Gastrointestinal Microbiome Composition in PD: A Pivotal Role of Covariates - Cosma-Grigorov, Alexandra; Meixner, Holger; Mrochen, Anne; Wirtz, Stefan; Winkler, Jürgen; Marxreiter, Franz (Frontiers in Neurology, 2020)
Altered gut microbiota may trigger or accelerate alpha-synuclein aggregation in the enteric nervous system in Parkinson's disease (PD). While several previous studies observed gut microbiota alterations in PD, findings like diversity indices, and altered bacterial taxa itself show a considerable heterogeneity across studies. We recruited 179 participants, of whom 101 fulfilled stringent inclusion criteria. Subsequently, the composition of the gut microbiota in 71 PD patients and 30 healthy controls was analyzed, sequencing V3–V4 regions of the bacterial 16S ribosomal RNA gene in fecal samples. Our goal was (1) to evaluate whether gut microbiota are altered in a southern German PD cohort, (2) to delineate the influence of disease duration, stage, and motor impairment, and (3) to investigate the influence of PD associated covariates like constipation and coffee consumption. Aiming to control for a large variety of covariates, strict inclusion criteria were applied. Finally, propensity score matching was performed to correct for, and to delineate the effect of remaining covariates (non-motor symptom (NMS) burden, constipation, and coffee consumption) on microbiota composition. Prior to matching altered abundances of distinct bacterial classes, orders, families, and genera were observed. Both, disease duration, and stage influenced microbiome composition. Interestingly, levodopa equivalent dose influenced the correlation of taxa with disease duration, while motor impairment did not. Applying different statistical tests, and after propensity score matching to control for NMS burden, constipation and coffee consumption, Faecalibacterium and Ruminococcus were most consistently reduced in PD compared to controls. Taken together, similar to previous studies, alterations of several taxa were observed in PD. Yet, further controlling for PD associated covariates such as constipation and coffee consumption revealed a pivotal role of these covariates. Our data highlight the impact of these PD associated covariates on microbiota composition in PD. This suggests that altered microbiota may mediate the protective effect of i.e., coffee consumption and the negative effect of constipation in PD.
CRIS-Team Scopus Importer:2020-10-16
Keywords: biomarker; constipation; covariates; gut; microbiome; non-motor symptoms; Parkinson's disease

Gastrointestinal microbiome in Parkinson's disease in a Bavarian cohort - Marxreiter, Franz; Cosma-Grigorov, Alexandra; Gaßner, Heiko; Meixner, Holger; Kohl, Zacharias; Neurath, Markus; Wirtz, Stefan; Winkler, Jürgen (2019)
EVALuna2:209001